Records and information management : fundamentals of professional practice - Saffady, William, 1944- (2021)
"This is the "go to" book for newly appointed records managers, as well as experienced records and information management (RIM) professionals who want a review of specific topics. The approach here is practical rather than theoretical and emphasizes best practices and published standards"--
Includes bibliographical references and index.
Keywords: Records -- Management; Archives -- Administration